Gender-Informing Aid for Trade : Entry Points and Initial Lessons Learned from the World Bank - Gamberoni, Elisa; Reis, José Guilherme (World Bank, Washington, DC, 2012)
The effects of policy interventions on women are of increasing concern to policy makers in all fields, and trade is no exception. This note reviews recent World Bank projects and studies that 'gender inform' trade-related interventions, and it uses the Bank's experience to promote gender-equal opportunities by highlighting entry points at which trade projects, studies, and policies can effectively address gender issues.